THE STRATEGY DEVELOPMENT AND COMPETITIVE ADVANTAGES OF MICRO SMALL MEDIUM ENTREPRISE BUSINESS INSTITUTION TOWARD REGIONAL DEVELOPMENT - Munandar, Andi (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
ABSTRACTThe implementation of âbusiness not as usualâ on the MP3EI 2011 â 2015 was held to optimize the potential of regional commodities that can increase the regional values. This research was conducted to search for the potential of UMKM in developing the potential commodities of Lampung province. The problems related to the commodities development consists of setting up the potential commodities which as based on the production copacity, so that it is difficult for those local governments to stimulate the coomdities development.The research method was qualitative method and data collected throughÂ Â literature reviews and analysis of competitive advantage. The results of the research were 1) there are high potential of UMKM development, 2)UMKM should be developed in accordance with the local culture and regional commodities, 3) UMKM plays an important role in solving the social problems such as creating employment, 4) the development of human resources, technology, capital, marketing, information and management plays an important role in the development micro business, 5) the natural resources, human resources, and the world market in the global era would be a high potential if it is designed and the initiation strategy consists of the government network, NGO, private institution, individual and groups, which is managed effectively.Â Keywords : strategy, business institutions, competitivve advantagesÂ Â Â STRATEGI PENGEMBANGAN DAN KEUNGGULAN BERSAING LEMBAGA BISNIS UMKM TERHADAP PEMBANGUNAN DAERAHÂ ABSTRAKPenerapan âbusiness not as usualâ pada MP3EI 2011-2025 dilakukan dengan menggali dan mengoptimalkan potensi unggulan daerah yang dapat memberikan nilai tambah bagi daerah tersebut. Penelitian ini dilakukan untuk mengkaji potensi Usaha Mikro Kecil dan Menengah (UMKM) dalam mengembangkan komoditas unggulan di Provinsi Lampung. Permasalahan terkait dengan pengembangan komoditas unggulan yang hanya didasarkan pada kapasitas produksi, sehingga menyulitkan bagi pemerintah daerah untuk menstimulir pengembangan komoditas unggulannya.Metode penelitian yang digunakan adalah metode kualitatif Â dan data yang dikumpulkan melalui studi literatur dan analisis keunggulan bersaing. Hasil penelitian adalah, Pertama; potensi pengembangan UMKM di daerah sangat besar. Kedua, pengembangan UMKM harus dilaksanakan sesuai dengan budaya lokal dan potensi yang dimiliki oleh daerah yang bersangkutan. Ketiga, sektor UMKM ini sangat berperan dalam menanggulangi masalah sosial di daerah dengan penyerapan tenaga kerja yang sangat tinggi. Keempat, peranan peningkatan SDM, pemanfaatan teknologi, akses permodalan, akses pemasaran, akses informasi, dan manajemen sangat penting dalam mengembangkan usaha mikro. Kelima; Sumber daya alam dan sumber daya manusia serta pasar dunia Â yang semakin terbuka pada era global merupakan potensi Â besar jika disain dan strategi replikasi yang meliputi kerjasama jaringan (network) pemerintah, LSM, lembaga swasta dan individu maupun kelompok dikelola secara efektif dalam bentuk kemitraan.Â Kata kunci :strategi,lembaga bisnis, keunggulan bersaing,